Given the functions:
![\begin{gathered} f(x)=5x+2 \\ g(x)=-2x^2-3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/9xr0vt9c6k4npde4mjmbbwvy6c13suh3ej.png)
• You need to find:
![f(-7)](https://img.qammunity.org/2023/formulas/mathematics/college/bgky6h7dkbmyioa3lh31byiztqh48lon6c.png)
Then, you have to substitute this value of "x" into the function "f" and then evaluate:
![x=-7](https://img.qammunity.org/2023/formulas/mathematics/college/lvk5kvk37o39xiby3yvk20443upwsjp2io.png)
Then, you get:
![f(-7)=5(-7)+2=-35+2=-33](https://img.qammunity.org/2023/formulas/mathematics/college/mn0fg4795s4422tk20p8h5akxraxdctp9j.png)
• Now you need to find:
![g(6)](https://img.qammunity.org/2023/formulas/mathematics/college/duchp6jme5rhnzt2ie5dy9tp6krauufc06.png)
Substitute this value of "x" into the function "g" and then evaluate:
![x=6](https://img.qammunity.org/2023/formulas/mathematics/college/i3rxl8c1ci3e808oua3cmlxzk41vuam7rn.png)
You get:
![g(6)=-2(6)^2-3=-2(36)-3=-72-3=-75](https://img.qammunity.org/2023/formulas/mathematics/college/1y8bdau7mh92cl446rf6ku5omvw9sex8la.png)
Hence, the answer is:
![\begin{gathered} f(-7)=-33 \\ g(6)=-75 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/gxjn3fgri6pwt43a5fzoqx6obtm3up618v.png)